Catechol‐containing waterborne polyurethane adhesive inspired by mussel proteins. Issue 46 (10th July 2021) - Ren, Longfang; Lin, Congcong; Lei, Pingchuan
Abstract: A series of waterborne polyurethane (PDMAPU) containing catechol group were prepared by double‐bond random copolymerization of terminated double bond polyurethane prepolymer with modified acrylamido dopamine under thermal initiation. This kind of mussel‐like waterborne polyurethane adhesive is inspired by marine mussel, as well as it is environment‐friendly and used in bonding of leather. FTIR and 1 H NMR proved the successful introduction of catechol group into polyurethane matrix. Oxidative cross‐linking between catechol unit and molecular chain in PDMAPU structure, the thermal stability and crystallization ability of PDMAPU was significantly improved. The increase of the particle size of PDMAPU emulsion showed that the introduction of catechol group changed the microstructure of polyurethane and enhanced the cross‐linking degree. The water resistance of polyurethane emulsion was further improved. Compared with PU without catechol group, the peel strength of leather substrate adhered by PDMAPU emulsion increased from 0.42 to 1.93 MPa, which indicated that PDMAPU has better bonding properties with leather. The bidentate hydrogen bond formed with catechol group as the reaction sites is considered to be the key reason for the adhesion of mussel‐like polyurethane adhesive to hydrophilic substrates. This work provides an alternative to prepare environment‐friendly high performance adhesive for hydrophilic substrates. Abstract : Waterborne polyurethane adhesive containing catechol structure is designed and synthesized by random copolymerization of double bond under thermal initiation. The mussel‐like waterborne polyurethane adhesive has better adhesion to leather substrate and has no solvent emission during use. The bidentate hydrogen bond formed with catechol as the reaction site enhanced the bonding properties of mussel polyurethane adhesive to hydrophilic substrate.